How the price of different breeds of feeder cattle has changed over time - Brazle, F.K.; Mintert, J.R.; Sartwelle, J. III; Bolze, R.P. Jr.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data on feeder steer characteristics, breeds, and prices were collected in 1986/87 and 1993 at Kansas and Missouri feeder cattle auctions to identify changes in buyers' preferences for various breeds. Results from models of feeder steer price/characteristics indicate that the relative value of many breeds changed over time. Relative to Hereford steers, Angus, Hereford × Angus cross, Continental cross, and low percentage Brahman steers all gained in price from 1986/87 to 1993. Longhorn Cross steers' price declined relative to Hereford steers over the same time period.
Keywords: Beef; Feeder steer; Prices; Feeder steer characteristics; Breeds